CYBERLITERATURE IN CHINA: LITERATURE AS INDUSTRY - Wati Wati; Hin Goan Gunawan (Fakultas Sastra Universitas Darma Persada, 2020)
The digital revolution has influenced the development of various industrial fields in China, as well as in literature. Various types of literary works were born in the digital space and later developed into a genre called Wǎngluò wénxué 网络 文学 or popularly known as